Nilai-Nilai Sosial pada Budaya Tarian Hegong dalam Prosesi Penyambutan Tamu di Desa Umauta, Kecamatan Bola, Kabupaten Sikka - Ajmin, Ajmin; Bryan A. P. Mapatha; Helena Mayesti; Atry Ine (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
The Hegong dance is one of the traditional dances that plays an important role in the welcoming procession in Umauta. However, in the midst of modernization, the sustainability of this dance faces challenges, especially in terms of dancer regeneration and community understanding of the cultural values contained therein. This study aims to identify strategies for preserving the Hegong dance and explore its potential for development in the tourism and creative economy sectors. The research method used is a qualitative approach with observation, interview, and literature study techniques. The results of the study indicate that preserving the Hegong dance requires synergy between the community, government, and cultural institutions through cultural education, arts training, and organizing cultural festivals. In addition, the use of digital media and the development of culture-based tourism can be effective strategies to expand the reach of promotion and increase the interest of the younger generation in this dance. In terms of economy, the production and marketing of art products related to the Hegong dance, such as costumes and souvenirs, have the potential to provide economic benefits to the local community. With a sustainable approach, it is hoped that the Hegong dance can continue to be preserved as part of the cultural identity of Umauta and become a tourist attraction that contributes to community welfare.